The ENEA′s 2019–2021 Three‐Year Research Project on Electrochemical Energy Storage. Issue 5 (7th February 2023) - Prosini, Pier Paolo; Aurora, Annalisa; Bozza, Francesco; Di Carli, Mariasole; Gislon, Paola; Moreno, Margherita; Paoletti, Claudia; Silvestri, Laura
Abstract: This work describes the research activities carried out by ENEA in the three‐year period 2019–2021 as a part of the Electrochemical Storage project. The project was part of a larger and more integrated project for energy storage, itself contained in the Electric System Research program. Within the project, various research lines were carried out: From the development of materials for electrodes to the testing of electrolytes and separators, both for lithium and sodium‐ion batteries, evaluation of the use of lithium metal batteries, and studying how to give a second life to used batteries. Dissemination of the results was an integral part of the program. The reasons that have been adduced to articulate the research plan and the main results obtained are reviewed in this concept. Abstract : ENEA research program : The paper contains a description of the research activities promoted by Agenzia nazionale per le nuove tecnologie, l'energia e lo sviluppo economico sostenibile (ENEA) to develop technologies for the construction of innovative batteries, improving their performance, safety, and sustainability. Research has been conducted on both lithium‐ion batteries and other more innovative chemistry, with the aim of systematically exploring the possible electrochemical storage technologies of the future. Reproduced from Ref. [43] Copyright (2020), with permission from The Authors.